Fathering the nation - Türköz, Meltem (Traditiones (Ljubljana), 2014)
This article provides an overview of the critical scholarship on the emergence and various stages of the veneration of Turkey's founder Mustafa Kemal Atatürk over the decades, demonstrating how specific political environments have played a role.
Keywords: Atatürk, Mustafa Kemal, 1881-1938; history; sociology; znamenite osebnosti; voditelji; personalities; nacionalism; nacionalizem; nationalism; narodna identiteta; secularism; javni spomeniki; Turčija; Turkey; zgodovinski pregledi